Germplasm characterization and selection indices in bread wheat (Triticum aestivum) for waterlogged soils in India - SINGH, GYANENDRA; SINGH, M K; TYAGI, B S; SINGH, J B; KUMAR, PRADEEP (The Indian Journal of Agricultural Sciences, 2017)
In a study, field screening of 109 elite Indian and exotic lines was carried out under normal and waterlogged soil conditions for two consecutive years (2012-13 and 2013-14). Results revealed high GCV along with high heritability and genetic advance for plant height and 1000-grain weight and these two traits were found most desirable in germplasm characterization for waterlogging tolerance. The geometric mean productivity (GMP), harmonic mean (HM), stress tolerance index (STI) and mean productivity (MP) were positively correlated with grain yield under stress (Ys) and non-stress conditions (Yp). There was a negative association between stress susceptible index and yield under normal conditions (Yp), whereas tolerance index (TOL) was positively correlated with Yp and negatively with yield under waterlogged conditions (Ys) during both the years (2012-13 and 2013-14). The promising lines, viz. BH 1146, DBW 39, DBW 52, NW 1014, NW 1067, NW 4081, PBW 621, PBW 631, PBW 590, RW 3684, HD 2967, HD 2997 and NW 4083 were selected on the basis of GMP, STI, MP, HM, and STS and rated as highly tolerant for waterlogged soils. However, the lines identified on the basis of stress susceptible index (SSI) and tolerance index (TOL) only could be suitable for normal and waterlogged conditions. The lines thus identified included; Perenjori, PBW 343, PBW 636, KRL 268, RAJ 4201, RAJ 4205 and WH 1094. It is anticipated that these lines will be utilized as donors for incorporation of waterlogging tolerance genes. The research findings also imply that tolerant lines eventually would lead to higher production and productivity under, heavy rainfall and prolonged stagnant water situations (adversely affect the wheat crop). These lines may also be utilized in hybridization programme for developing next generation mapping (MAGIC and NAM) populations for fine QTLs scanning for waterlogging tolerance.